The Rise and Fall of the « Fourth Empire of the St. Lawrence » : the Québec-Labrador Iron Ore Mining Region - Bradbury, John (Cahiers de géographie du Québec, 1985)
This paper is based upon a discussion of the rise and fall of the iron ore mining industry in the Labrador trough of the Québec-Labrador region. The growth of exploration, development, expansion and decline phases are noted over the period between 1950 (circa) to 1984. Reference is made to the single industry nature of the industrialization process in the region and to the absence of long-term industrial growth.